A novel polysaccharide isolated from Ulva Pertusa: Structure and physicochemical property. (1st April 2020) - Gao, Xin; Qu, Hang; Shan, Shan; Song, Chen; Baranenko, Denis; Li, Yongzhi; Lu, Weihong
Highlights: A novel polysaccharide UPP was isolated from Ulva Pertusa . The structural characterization of UPP was identified by NMR. UPP was a semi-crystalline polymer without triple-helical structure. Abstract: A new water-soluble polysaccharide UPP was obtained from Ulva Pertusa and its structure was studied. The structural analysis results showed that UPP was composed of eight residues. The bone structure of UPP was →4)-β-D-Xylp-(1→4)-α-L-Rhap3S(1→3, 4)-β-L-Arap(1→3)-α-L-Rhap(1→2, 4)-α-L-Rhap(1→4)-α-D-Galp(1→ and there were two main branches. The branch structure at the 3-position of 1, 3, 4-β-L-Arap was →3, 4)-β-L-Arap(1→4)-β-D-Glcp3Me(1→4)- β-D-GlcpA(1→ and the branch structure at 2-position of 1, 2, 4-α-L-Rhap was →4)-β-D-GlcpA(1→4)-β-D-Xylp(1→. In addition, the physicochemical property analysis showed that UPP was a semi-crystalline polymer and there was no triple-helical structure. This structure analysis of UPP will be beneficial for future research on the algal polysaccharides.